Saccadic Disinhibition on the Saccade Trace - Hongmei Yan; Hao Zhang (i-Perception, 2011)
It has generally thought that information from the eyes is made available during a fixation, but not during a saccade when reading. Some researchers even suggested the duration of saccades should be subtracted from the reading time in eye movement research. During a saccadic eye movement, visual sensitivity is greatly reduced, this phenomenon called saccadic suppression, which let us unaware of blurred motion images produced by saccades and are not disturbed by them. Actually, we frequently make saccadic eye movement during reading, however, the exact function of saccades except redirecting the fovea to objects of interest still remain unknown. In this research, a two-alternative forced-choice character detection task was used to investigate the sensitivity of perception during saccade execution. The experimental results showed that the accuracy of character perception during saccades is indeed lower compared with fixation situation. However, the perception accuracy on the trace of saccades is remarkably higher than that of nonsaccade-trace, which indicated a saccadic disinhibiton on the saccade trace. Our research proved that visual information might also be processed in a certain extent during saccade onset.